1985
DOI: 10.1037/0022-006x.53.5.647
|View full text |Cite
|
Sign up to set email alerts
|

Depression in children: Prevalence and correlates.

Abstract: The present research assessed the prevalence of severe depression in children according to four risk variables: sex, age, intellectual functioning, and family income. Also investigated was a set of variables theoretically associated with the construct of childhood depression. Data were gathered from 3,020 normal elementary school children by means of peer nominations, self-ratings, teachers' observations, and pupil personnel records. In addition, data from 508 of the children's mothers were obtained from an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
46
2
7

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 29 publications
12
46
2
7
Order By: Relevance
“…Poverty was effective on depressive symptoms in children (Table 2). Poverty and dif- (5,13,24,37,38) showed that low economic status increases depression. It can be concluded that low economic status leads to depression via deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Poverty was effective on depressive symptoms in children (Table 2). Poverty and dif- (5,13,24,37,38) showed that low economic status increases depression. It can be concluded that low economic status leads to depression via deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…En primer lugar, en el caso del PNID, se observan promedios más bajos en la puntuación de la subescala de depresión de esta prueba que en el trabajo de Ezpeleta et al (1990) ya mencionado, y equiparable para la submuestra de Sevilla en la investigación nacional de PolainoLorente y Doménech (1988;1990). En segundo lugar, diferentes aportaciones coinciden en las bajas correlaciones halladas entre dicho instrumento y el inventario GDI (entre 0'12 y 0'23) (Lefkowitz y Tesiny, 1985;Marujo y Da Silva, 1999;), e incluso sin correlación estadísti-camente significativa (Ezpeleta et al, 1990). En el presente trabajo, la correlación entre dichos instrumentos resulta significativa aunque con una puntuación francamente modesta (0'14), de acuerdo con los estudios citados y, probablemente, efecto también del gran tamaño de la población participante.…”
Section: Discussionunclassified
“…(35,36) , Lefkowitz ve Tesiny (1985)'in çalışmaları ile çelişmektedir (37). Bu sonuçlara göre, gelir düzeyi iyi olmayan güreşçi öğrenciler için; başarılı sporcular olmayı hedefleyebilme ve kendilerini yeterli hissedebilme adına daha iyi koşullar içeren yaşam standartlarının geliştirilmesinin ve psikolojik destek sağlanmasının gerekli olduğu düşünülebilir.…”
Section: Tartişma Sonuçunclassified